Perancangan Buku Ilustrasi Pengaruh Positif Hewan Peliharaan Pada Psikologi Anak - Girsang, Holly Natalyn Esahita Br; Kurniawan, Ivan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
Humans have various views about pets. Pets are animals that have been tamed and live side by side with humans. Information about the influence of pets on the psychology of children is not widely disseminated. Psychology is an important thing in human life. However, people do not understand psychology. Pets have an influence on a child's psychology which includes social, mental, mental, and physical. Pets can help children practice various positive things through activities that are done together. Pets have no breed limit to keep. The types of pets in this design are dogs, cats, rabbits, hamsters, and fish. The number of people who do not care and understand about psychology is the basis of the problem. Illustrated books become media in the design that provide information about children's activities with pets and their effects on children.